Neap-spring tidal effects on dissolved oxygen in two Malaysian estuaries - Nelson, Bruce W.; Sasekumar, A.; Ibrahim, Zelina Z. (Springer, 1994)
The longitudinal distributions of dissolved oxygen change dramatically during neap-spring tidal cycles in the lower Selangor and Klang Rivers. An oxygen deficit develops in both estuaries when the tidal range is high. The Selangor River inflow is nearly saturated with D.O., but during spring tides D.O. falls to as little as 15% of saturation in the middle reaches of the estuary. The Klang River has low D.O. freshwater input, an oxygen minimum develops during neap tides, and anoxic conditions are produced by spring tides. These oxygen minima are attributed to the high oxygen demand of sediment that rests on the bottom during neap tides and is resuspended during spring tides. The ecological effects of tidal cycling patterns of dissolved oxygen in these Malaysian estuaries need further study, within the context of land use patterns and other human activities.